Appendiceal Mucocele Diagnosed in Patients with Inflammatory Bowel Disease Using Endoscopic Ultrasound. (3rd July 2012) - Wong, Uni; Darwin, Peter
Abstract : When a bulging appendiceal orifice is observed during surveillance colonoscopy, the possibility of appendiceal mucocele must be considered. Appendiceal mucocele is a rare group of lesions characterized by mucinous distension of the appendiceal lumen with the dangerous potential to rupture, resulting in the development of pseudomyxoma peritonei. Early recognition and diagnosis of appendiceal mucocele can prevent the dreaded complication of pseudomyxoma peritonei but it requires a high index of suspicion. Patients with inflammatory bowel disease are at increased risk for colorectal neoplasm but neoplasm of the appendix is infrequently reported. We report two of the first cases of appendiceal mucoceles diagnosed in patients with inflammatory bowel disease using endoscopic ultrasound.